2013
DOI: 10.1111/hepr.12124
|View full text |Cite
|
Sign up to set email alerts
|

Full genome analysis of Philippine indigenous subgenotype IA hepatitis A virus strains from Japanese patients with imported acute hepatitis A

Abstract: These results indicate that HAV isolates belonging to the IA-2 lineage might have been imported from the Philippines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Three HAV isolates of Cluster 1 shared 98.5–98.7% identities over the entire genome, while the mean identities between the four distinct clusters were 96.2–97.3%, further supporting the validity of the clustering (Supplementary Table SIV). As shown in Figure , the phylogenetic tree constructed based on the entire genome also confirmed that the six Mongolian HAV isolates of the four clusters obtained in the present study are classifiable into subgenotype IA and further into an Asian IA lineage, consisting of HAV strains from China, Indonesia, Japan, Malaysia, Papua New Guinea, Philippines, Singapore, and Thailand [Fujiwara et al, ; Hu et al, ; Watanabe et al, ; Mulyanto et al, ; Ishii et al, ], with a bootstrap value of 100%. This tree also revealed that the polyphyletic IA strains are circulating in Mongolia.…”
Section: Resultssupporting
confidence: 79%
“…Three HAV isolates of Cluster 1 shared 98.5–98.7% identities over the entire genome, while the mean identities between the four distinct clusters were 96.2–97.3%, further supporting the validity of the clustering (Supplementary Table SIV). As shown in Figure , the phylogenetic tree constructed based on the entire genome also confirmed that the six Mongolian HAV isolates of the four clusters obtained in the present study are classifiable into subgenotype IA and further into an Asian IA lineage, consisting of HAV strains from China, Indonesia, Japan, Malaysia, Papua New Guinea, Philippines, Singapore, and Thailand [Fujiwara et al, ; Hu et al, ; Watanabe et al, ; Mulyanto et al, ; Ishii et al, ], with a bootstrap value of 100%. This tree also revealed that the polyphyletic IA strains are circulating in Mongolia.…”
Section: Resultssupporting
confidence: 79%
“…Although the IIIA outbreak in the Tohoku region was restricted to a small region from week 5 to 7 and subsequently replaced by 2014JapanIA-EPM, we must acknowledge the possibility that the subgenotype IIIA strain has also recently become a locally circulating strain in Japan. Previously, we found that the multi-location outbreak of hepatitis A in the spring of 2010 was caused not only by locally circulating strains, but also by two HAV strains that may be related to Philippines (IA-2) and Korea (IIIA) strains [13,27]. The 2010 HAV outbreak can be attributed to introduction of HAV strains from two newly emerged lineages that were relatively rare in Japan until 2009 [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…These strains were close to 2 Japanese HAV strains, AB793726 and AB973401, with nucleotide sequence identities of 96.5%-98.8% and 97.4%-99.1%, respectively. Strain AB793726 was detected in a Japanese patient in 2012, and it is considered to have been imported from the Philippines (12). Strain AB973401 was isolated from a Japanese patient during a mini-epidemic in 2010 and has a nucleotide sequence that is identical to that of strain EU825856, which was isolated from a German patient who developed acute hepatitis after traveling to the Philippines (13).…”
mentioning
confidence: 99%